Barriers to and Facilitators of Engagement With mHealth Technology for Remote Measurement and Management of Depression: Qualitative Analysis - Simblett, Sara; Matcham, Faith; Siddi, Sara; Bulgari, Viola; Barattieri di San Pietro, Chiara; Hortas López, Jorge; Ferrão, José; Polhemus, Ashley; Haro, Josep Maria; de Girolamo, Giovanni; Gamble, Peter; Eriksson, Hans; et al. (JMIR mHealth and uHealth, 2019)
BACKGROUND: Mobile technology has the potential to provide accurate, impactful data on the symptoms of depression, which could improve health management or assist in early detection of relapse. However, for this potential to be achieved, it is essential that patients engage with the technology. Although many barriers to and facilitators of the use of this technology are common across therapeutic areas and technology types, many may be specific to cultural and health contexts. OBJECTIVE: This study aimed to determine the potential barriers to and facilitators of engagement with mobile health (mHealth) technology for remote measurement and management of depression across three Western European countries. METHODS: Participants (N=25; 4:1 ratio of women to men; age range, 25-73 years) who experienced depression participated in five focus groups held in three countries (two in the United Kingdom, two in Spain, and one in Italy). The focus groups investigated the potential barriers to and facilitators of the use of mHealth technology. A systematic thematic analysis was used to extract themes and subthemes. RESULTS: Facilitators and barriers were categorized as health-related factors, user-related factors, and technology-related factors. A total of 58 subthemes of specific barriers and facilitators or moderators emerged. A core group of themes including motivation, potential impact on mood and anxiety, aspects of inconvenience, and ease of use was noted across all countries. CONCLUSIONS: Similarities in the barriers to and facilitators of the use of mHealth technology have been observed across Spain, Italy, and the United Kingdom. These themes provide guidance on ways to promote the design of feasible and acceptable cross-cultural mHealth tools.
Keywords: senioři; Italy; deprese; depression; Telemedicine; telemedicína; Depression; Middle Aged; mužské pohlaví; Spojené království; Adult; zapojení pacienta; Španělsko; mHealth; kvalitativní výzkum; Focus Groups; Qualitative Research; ženské pohlaví; Humans; Spain; qualitative; zjišťování skupinových postojů; barriers; lidé středního věku; Patient Participation; United Kingdom; Itálie; dospělí; acceptability; facilitators; feasibility; Female; Aged; lidé; Male